유채 봄 재배 기계이식을 위한 품종별 육묘 일수에 따른 묘소질 평가 - 안다희; Da-hee An; 차영록; Young-lok Cha; 김광수; Kwang-soo Kim; 신운철; Woon-chul Shin; 이지은; Ji-eun Lee (Korean journal of crop science, 2021)
Rapeseed (Brassica napus L.) is generally sown in late autumn and harvested in early summer in Korea, however, spring cultivation has also been attempted in some areas because frequent climate changes induce reducing productivity. Therefore, there is a need for a transplanting technology that is relatively easy to control of cropping season according to changes in cultivation conditions. In this study, to find out the optimal characteristics of seedlings for machine transplanting of spring cultivation, seedling morphological characteristics were investigated according to the seedling age of three varieties for 2020 and 2021. The hypocotyl length was less than 2 cm in both years and the 40-day-old seedling was the shortest among all seedling ages. The number and size of leaf were increased with longer seedling age in both years. To evaluate seedling quality, total seedling length, seedling weight, and impact resistance were measured before transplanting. Total seedling length was the longest in 40-day-old seedlings and the shortest in 25-day-old seedlings in both years. In the case of seedling weight, no significant differences were observed depending on the seedling age and the impact resistance increased with increasing seedling age. Finally, ‘Jungmo7001’, ‘Naehan’, and ‘Tamla’ showed a high transplanting rate in seedlings grown for more than 30 days, 35 days, and 40 days, respectively, in the field using a general transplanter. These results suggest that the proper seedling age for transplanting is limited depending on the rapeseed varieties. The suitable seedling cultivation method can be selected for different cultivation environments.